Introduction to the Pharmacist Profession and Education on Wise Choice of Snacks and the Dangers of Cigarettes and Drugs for Teenagers - Renggana, Hesti; Susanti, Risa; Qowiyyah, Atun; Dewi, Asri; Winda, Deden; Anshar, Doni; Sadino, Asman (Fakultas Kewirausahaan Universitas Garut, 2024)
Pharmacists are competent health professionals in drug management. Many efforts have been made so that the role of pharmacists in carrying out pharmaceutical work is more felt in the community. Therefore, community service is carried out in the form of education on introducing the pharmacist profession, wisely choosing snacks, and about the dangers of cigarettes and drugs. It is expected that from this service, students who are part of the community can better understand the pharmacist profession and its role in adolescent health. Education was carried out on MIT and MTs Baitul Aziz Majalaya students. Before the education, a pretest was carried out and after the education, a posttest was carried out using a questionnaire related to the material. Data were processed and analyzed using descriptive statistics. The results of the education showed that the level of knowledge of MIT students increased, especially in the good category, from 8% to 76% for knowledge of the pharmacist profession, and from 80% to 95% for knowledge of wisely choosing snacks. In addition, the level of knowledge of MTs students regarding the dangers of cigarettes and drugs also increased, especially in the good category from 13% to 75% after education.